Quantifying epitope presentation using mass spectrometry. Issue 2 (December 2015) - Croft, Nathan P.; Purcell, Anthony W.; Tscharke, David C.
Highlights: Quantifying MHC-peptide (pMHC) abundance is key to understanding immunogenicity. Direct and indirect quantification of pMHC amounts can be done by several methods. Mass spectrometry provides direct and precise absolute pMHC quantification. Only mass spectrometry will allow proteome-wide quantification of pMHC abundance. Abstract: Understanding the absolute quantities of MHC-bound epitopes (pMHC) presented on the surface of cells has long been a critical missing element in our knowledge of antigen presentation to T cells. Until recently, attaining such information has been restricted to the use of pMHC complex-specific monoclonal antibodies or T cell assays probing fractionated peptides eluted from cells. Although successful in a variety of cases, such approaches are limited in their scope and feasibility due to the nature of the reagents they are reliant upon. Here we report on the advancement of targeted mass spectrometry techniques to provide simultaneous and direct measurements of the relative and absolute levels of pMHC molecules and its potential for impact upon the field of antigen processing and presentation.